Why Is a High Temperature Needed by Thermus thermophilus Argonaute During mRNA Silencing: A Theoretical Study - Liu, Ye; Yu, Zhengfei; Zhu, Jingxuan; Wang, Song; Xu, Dong; Han, Weiwei (Frontiers in Chemistry, 2018)
Thermus thermophiles Argonaute (TtAgo) is a complex, which is consisted of 5′-phosphorylated guide DNA and a series of target DNA with catalytic activities at high temperatures. To understand why high temperatures are needed for the catalytic activities, three molecular dynamics simulations and binding free energy calculations at 310, 324, and 338K were performed for the TtAgo-DNA complex to explore the conformational changes between 16-mer guide DNA/15-mer target DNA and TtAgo at different temperatures. The simulation results indicate that a collapse of a small β-strand (residues 507–509) at 310 K caused Glu512 to move away from the catalytic residues Asp546 and Asp478, resulting in a decrease in catalytic activity, which was not observed in the simulations at 324 and 338 K. The nucleic acid binding channel became enlarged at 324 and 338K, thereby facilitating the DNA to slide in. Binding free energy calculations and hydrogen bond occupancy indicated that the interaction between TtAgo and the DNA was more stable at 324K and 338K than at 310 K. The DNA binding pocket residues Lys575 and Asn590 became less solvent accessible at 324 and 338K than at 310 K to influence hydrophilic interaction with DNA. Our simulation studies shed some light on the mechanism of TtAgo and explained why a high temperature was needed by TtAgo during gene editing of CRISPR.